Mechanical and bioactivity properties of ti-ha-xnb alloy matrix composite produced via powder metallurgy route for bone implant / Farrah Noor Ahmad ... [et al.] - Noor Ahmad, Farrah; Hussain, Zuhailawati; Mohd Nasir, Siti Shareeda; Mohd Noor, Nurul Muthmainnah; Mohd Fohmi, Nor Azirah (2020)
Titanium is the most popular metallic implant for orthopedic by virtue of its excellence in mechanical properties. Nevertheless, the mismatch of elastic modulus and its bioinert behaviour have been identified as the major reasons for implantation failure. The present work investigates the mechanical performances and bioactivity of titanium-niobium-hydroxyapatite (Ti-Nb-HA) composite prepared by mechanical alloying and powder metallurgy with Nb ranging from 0 to 40 wt.%. Ti, Nb and HA powders were mixed in a planetary mill for 2 hours at 200 rpm, followed by compaction under 500 MPa and sintering at 1200 °C. Higher Nb content increased compressive strength (199.95 MPa to 300.11 MPa) and microhardness (120.97 HV to 269.90 HV) due to solid solution strengthening. However, the presence of TiO2 and Ti2P decreases compressive strength at 40 wt.% Nb. With the rise of Nb content, the elastic modulus was slightly decreased. The highest amount of β phase is obtained by 30 wt.% Nb (76%). Upon immersion test in HBSS for 30 days, the highest bioactivity was attained by 30 wt.% Nb. The composite with an addition of 30 wt.% Nb displayed the best properties with higher potential to provide mechanical support and bioactivity enhancement in getting similar cortical bone characteristics.